2010
DOI: 10.3109/08958378.2010.483258
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke-induced effects on bone marrow B-cell subsets and CD4+:CD8+T-cell ratios are reversed by smoking cessation: Influence of bone mass on immune cell response to and recovery from smoke exposure

Abstract: Cigarette smoking adversely affects the immune system, and is a risk factor for developing osteoporosis. How smoking contributes to osteoporosis is unclear, but since lymphocytes help maintain bone homeostasis and lymphocyte depletion results in bone loss, one potential mechanism for how smoke exposure promotes osteoporosis is by reducing bone marrow lymphocytes. Since the risk for developing osteoporosis is reportedly greater in smokers with polymorphisms in LRP5, a gene involved in canonical Wnt signaling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 39 publications
(51 reference statements)
3
36
1
3
Order By: Relevance
“…A reason why current smoking could be protective against pSS could be a suppressing effect of smoking on the B cells directly or by reduced production of B-cell activating factor [49, 50]. In predisposed individuals who stop smoking, taking away the inhibitory effect of cigarette smoke on the B cells could lead to activation of autoreactive B cells that might trigger the development of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A reason why current smoking could be protective against pSS could be a suppressing effect of smoking on the B cells directly or by reduced production of B-cell activating factor [49, 50]. In predisposed individuals who stop smoking, taking away the inhibitory effect of cigarette smoke on the B cells could lead to activation of autoreactive B cells that might trigger the development of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke has a well-established role in susceptibility to autoimmune diseases, making a biological effect on the immune system highly probable [42]. Animal models have suggested that smoke exposure affects several compartments of the immune system, including innate immunity, B- and T-lymphocytes, and natural killer cells [43], [44], [45]. In rheumatoid arthritis, an autoimmune disease in which smoking is important in determining susceptibility, an interaction was identified between HLA alleles, cigarette smoking and immunity to α-enolase [46].…”
Section: Discussionmentioning
confidence: 99%
“…They developed from bone marrow-derived hematopoietic stem cells that first differentiated into precursor and progenitor B cells and then immature B cells [82]. It was found that tobacco smoke exposure led to obvious downregulation of murine marrow B220 + CD34 − pre-B cells and/or B220 + CD34 + pro-B cells without significant changes in cell apoptosis and cell cycle [83, 84]. …”
Section: Effects Of Cigarette Smoking On Adaptive Immunitymentioning
confidence: 99%